IKLIM SEKOLAH YANG MENDUKUNG PENGETAHUAN DAN SIKAP LINGKUNGAN WARGA SEKOLAH (STUDI KASUS DI SMAN 2 WAJO) - Mustikawati, Mustikawati; Mithen, Mithen; Sahabuddin, Erma Suryani (UNM Environmental Journals, 2023)
This study aims to describe the management of the school climate that supports school members' environmental knowledge and attitudes. This study was conducted at SMA Negeri 2 Wajo, involving the principal and teachers as informants. Data was collected through interviews and observations to find aspects of managing the school environment. These aspects include school conditions, classrooms, canteens, toilets, and waste management. The study results in show that managing the school climate that supports knowledge of the environmental attitudes of school members is supported by development policies to create school conditions. This policy is carried out by developing student participation in maintaining the school environment. Furthermore, maintenance of clean classroom facilities, free of waste, comfortable and neatly arranged, is achieved by the knowledge and attitude of school members. The school principal also implements regulations for providing school canteen facilities that provide healthy food. The most critical school facility is the toilet which is always clean and comfortable. As well as waste management with the application of 3R, namely Reduce, Reuse, and Recycle.